1995
DOI: 10.1210/jcem.80.8.7543116
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of insulin-like growth factor (IGF)-binding protein-3 (IGFBP-3) in healthy infants, children, and adolescents: the relation to IGF-I, IGF-II, IGFBP-1, IGFBP-2, age, sex, body mass index, and pubertal maturation.

Abstract: Circulating IGF-I and -II are bound to specific insulin-like growth factor (IGF)-binding proteins (IGFBPs), of which IGFBP-3 binds the majority of the IGFs. IGFBP-3 levels are regulated by GH and have been suggested to provide additional information on GH secretory capacity compared to IGF-I. However, the diagnostic value of IGFBP-3 is still controversial, perhaps because the quality of the available normative data for IGFBP-3 varies. It has recently been shown that a large number of individuals is required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
1
7

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(131 citation statements)
references
References 29 publications
10
106
1
7
Order By: Relevance
“…54 Another possibility is an endocrine etiology, since height is correlated with serum hormones that may play a role in carcinogenesis. 55,56 It also may be possible that a behavioral correlate of body height is related to sun exposure, such as participation in outdoor sporting activities, 57 that increases the likelihood of developing melanoma. However, our adjustment for sun exposure-related factors generally had little to no effect on our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54 Another possibility is an endocrine etiology, since height is correlated with serum hormones that may play a role in carcinogenesis. 55,56 It also may be possible that a behavioral correlate of body height is related to sun exposure, such as participation in outdoor sporting activities, 57 that increases the likelihood of developing melanoma. However, our adjustment for sun exposure-related factors generally had little to no effect on our results.…”
Section: Discussionmentioning
confidence: 99%
“…55,56,58 Accumulating evidence suggests that adult weight gain may be a more relevant variable to assess the effect of weight on health than body weight or BMI. 59 We cannot explain why the association with weight gain was stronger for melanomas on the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of IGF-I and IGFBP-3 exhibit little diurnal variation (Jorgensen et al, 1990) and reflect endogenous GH secretion in healthy children (Blum et al, 1993). In addition to GH status, chronological age, gonadal maturation and nutrition also have influence on IGF-I concentration significantly (Bouhaddioui et al, 1989;Lopez-Jaramillo et al, 1992;Juul et al, 1994Juul et al, , 1995. It has been demonstrated that plasma IGF-I levels are lower in malnourished children (Unterman et al, 1985;Bouhaddioui et al, 1989;Wan Nazaimoon et al, 1996;Beaune et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Since IGFs are regulated by both endocrine and paracrine mechanisms, the action of IGFs in tissue, however, is determined not only by the circulating levels of IGFs and IGF-binding proteins (IGFBPs), but also by local production (Jones and Clemmons, 1995). There is a large interpersonal variability in the circulating concentrations of IGF-I and IGFBP-3 (a major IGFBP in the circulation) (Juul et al, 1994(Juul et al, , 1995.…”
mentioning
confidence: 99%